Effect of Hydrogen Insertion on the Optical Properties of PD-Coated Magnesium Lanthanides - Klaus von Rottkay; Michael D. Rubin; Franck Michalak; Robert D. Armitage; Thomas J. Richardson; Jonathan L. Slack; Peter A. Duine (Electrochimica Acta, 1998)
Metallic magnesium lanthanide thin films upon insertion of hydrogen transform to a highly transparent hydride phase. With a Pd overlayer, the transformation can be produced either by electrochemical insertion of hydrogen or by exposing the film to hydrogen gas. Unlike amorphous oxide electrochromics, the transformation is accompanied by a large change in visible reflectance (about 50%). The optical switching effect in these materials is investigated in terms of changes in the complex refractive index as determined by variable-angle spectroscopic ellipsometric and normal-incidence radiometric measurements over the solar spectrum. Furthermore the optical effect of converting the Pd caplayer to Pd-H was determined. It is shown that the pd layer limits the visible transmittance of the hyrdrided stack to about 35-40%. Whereas the extinction coefficient of the dehydrided LnMg-layers at 550 nm is between 2.2 and 3.1, it is as low as 10-4 in the transparent state.

Electrochromic Lithium Nickel Oxide Thin Films by RF-Sputtering from a LiNiO2 Target - Franck Michalak; Klaus von Rottkay; Thomas J. Richardson; Jonathan L. Slack; Michael D. Rubin (Electrochimica Acta, 1998)
Thin films of lithium nickel oxide were deposited by rf sputtering from a stoichiometric LiNiO2 target. The composition and structure of these films depended on the oxygen pressure during deposition (sputtering gas is Argon), and, to a certain extent, the target history. The sputtering geometry, i.e. the substrate to target distance and the sputtering angle were also critical. the films exhibit excellent reversibility in the potential range 1.1V to 3.8 V vs Li/Li+ and could be cycled in a liquid electrolyte half cell for more than 3000 cycles with a switching range ΔTvis close to 70%. The coloration efficiency in the visible was typically -30 to -40 cm2 C-1. The switching performance of a device utilizing a lithium nickel oxide film as counter electrode for a tungsten oxide electrochromic film is reported.

Tungsten-Vanadium Oxide Sputtered Films for Electrochromic Devices - Thomas J. Richardson; Klaus von Rottkay; Jonathan L. Slack; Franck Michalak; Michael D. Rubin (Electrochemical Society: Molecular Functions of Electroactive Thin Films, 1998)
Mixed vanadium and tungsten oxide films with compositions ranging from 0 to 100% vanadium (metals basis) were prepared by reactive sputtering from metallic vanadium and tungsten targets in an atmosphere of argon and oxygen. The vanadium content varied smoothly with the fraction of total power applied to the vanadium target. Films containing vanadium were more color neutral than pure tungsten oxide films, tending to gray-brown at high V fraction. The electrochromic switching performance of these films was investigated by in situ monitoring of their visible transmittance during lithium insertion/extraction cycling in a non-aqueous electrolyte (1M LiClO4 in PC). the solar transmittance and reflectance was measured ex-situ. Films with vanadium content greater than about 15%, exhibited a marked decrease in switching range. The coloration efficiencies followed a similar trend.